Data-Focused Approach: Developing A New Intervention Method In Applied Psychology - Widiastuti, Tiara R.; Asitasari, Walida; Prawitasari*, Johana E (Faculty of Psychology, Universitas Gadjah Mada, 2019)
This study aimed to compare the newly developed psychological intervention method by the first author, named data-focused approach, to the more classical process-oriented approaches, i.e., gestalt, psychodynamics, and interactional group psychoÂtherapies. A pretest-posttest design was used. Twenty-one participants were assigned into four experimental groups. Measures used were self-regulation, emotional awareness, and meta-emotion scales as well as stated agenda on interpersonal relationships. They were administered before and after therapy sessions. Results indicated that the new method was evidently compatible with the classical psychotherapy approaches. Specifically, participants in the data-focused approach were satisfied with the aiming of behavioral change in their interpersonal relationships. The new approach is effective to be applied in group processes. Thus, this new method is also recommended to be studied in other settings. Using the simplified procedure, it is hoped that other professionals, like medical doctors, nurses, midwifes, women activists in public health centers may use it to provide better service for the community.